Genomic population structure and conservation of the red listed Carabus arcensis (Coleoptera: Carabidae) in island–mainland habitats of Northern Europe. Issue 3 (23rd October 2017) - Hansen, Aslak Kappel; Justesen, Mathias Just; Olsen, Morten Tange; Solodovnikov, Alexey
Abstract: Larger carabid beetle species linked to open habitats have exhibited recent rapid decline in numbers throughout Europe. For example, Carabus arcensis is on the Danish Red List. Ability of C. arcensis to disperse across non‐habitable barriers in an island–mainland landscape has been evaluated through investigation of its population structure across Kattegat strait with special emphasis on the oceanic island Læsø. Based on admixture and statistical phylogenetic analyses of genome‐wide SNPs, data for C. arcensis comprising 3195 SNPs in 87 individuals from nine sample sites, three major lineages and six populations were found within the study area. These are the first genome‐wide SNPs data generated for carabid beetles. Contrary to predicted, water stretches did not seem to affect dispersal of C. arcensis to the island of Læsø, as isolation by distance plot showed no differences between sites connected by land and sites separated by an oceanic water gap. Unexpected high genetic diversity of the C. arcensis population on Læsø island has been observed calling for future research and explanation. High conservation priority in Denmark is suggested for smaller islands like Læsø.